Anthurium tacotalpense (Araceae), a new species from Mexico - Pérez-Farrera, Miguel Ángel; Díaz Jiménez, Pedro; Croat, Thomas B.; Hentrich, Heiko; Padilla Vega, José; Aguilar-Rodríguez, Pedro A. (Phytotaxa, 2022)
Anthurium tacotalpense a new species of genus Anthurium sect. Andiphilum from Tabasco, Mexico is described and illustrated. The new species is morphologically similar to Anthurium cerrobaulense but it differs from that species in having adaxially flattened petioles, spadix up to twice as long and immature berries green, orange when mature.